THE USE OF SPOTIFY APPLICATION TO IMPROVE STUDENTS ABILITY IN LISTENING THROUGH ENGLISH SONG: A Pre-Experimental Research - Andriani; Akib, Erwin; Ma'ruf, Amar (Journal of Computer Interaction in Education, 2018)
This research aimed at finding out the improvement of the students’ listening ability in listening skill by using SPOTIFY Application as a tool that focused on Listening English song to identify what words the singer said and the meaning of the song. The researcher applied pre-experimental method with one group pre-test - post-test design, and collected the data based on the test. The sample of the research was the first semester students, which consisted of 25 students. The sample was taken by using purposive sampling technique. The research findings showed that the first semester students of English Department of Muhammadiyah University of Makassar had fairly score in pre-test. After treatment, their listening ability in identify phoneme words increase significantly. The result of the research were the mean score obtained by the students through pre-test was 57.2 and posttest was 74.4 with the t-test value orientation is greater than t-table (10.8>2.06). Listening through English Song in term of identify the phoneme words improved 17.2%. The result of calculating t-test of the indicators in the students’ t–test listening ability in listening through English Song was greater than t-table 25.1>2.06. Eventually, based on findings and discussion above, the researcher concluded that the improvement of the students listening ability through English song using SPOTIFY Application was significant improved